Sentiment's Stock Impact: Company Size's Role In Stock Price Dynamics - Humairoh Zahra; Bandi Bandi (Al-Makki Publisher, 2024)
This study aims to present empirical evidence on the impact of investor sentiment on stock prices, test the moderating effect of firm size on the relationship between investor sentiment and stock prices, and examine potential differences in this relationship across firms of varying sizes. The sample for this study consists of 246 companies listed on the main board of the Indonesia Stock Exchange from 2018 to 2022. EViews 12 were used for data processing. The findings of the study suggest that investor sentiment has a positive impact on the stock prices of firms traded on the Indonesia Stock Exchange. Additionally, the relationship between investor sentiment and stock prices is not moderated by company size, although the effect of investor sentiment on stock prices varies across different company sizes.